Effects of Rice Husk Ash (RHS) Produced from Different Temperatures on the Performances of Concrete - Leong, Tuck Lun (2015)
This project is about the addition of Furnace Incinerated Rice Husk Ash (RHA) into blended cement. The primary objective of this project is to investigate the mechanical properties of blended cement after RHA was used to replace cement partially at the ratio of 2.5 %, 5.0 %, 7.5 % and 10.0 %. The physical and chemical properties of RHA were determined by Particle Size Analyzer and Fourier Transform Infrared Spectroscopy (FTIR) Analysis. The pozzolanic reactivity of RHA is highly depended on the silica form. The silica form in the RHA is determined by the incineration process to decide if it is under amorphous form or crystalline form. It was that the optimum cement replacement ratio of RHA incinerated at the temperature of 600 °C and 700 °C both were at 5 %.